Respuesta :

Answer:

2 2/3

Step-by-step explanation:

3 5/6+(−1 1/6)

= 3 5/6 - 1 1/6

= 2 4/6 = 2 2/3

qenl

The result of 3 5/6+(−1 1/6) is 2 2/3.

INTRODUCTION

The definition of a fraction is that the division of two integers by the number being divided is called the numerator and the divisor is called the denominator.

Kinds of Fractions:

  • a. Mixed fractions, for example: 1⅘, 2½, 3⅔, etc.
  • b. Common fractions, for example: , , , etc.
  • c. Percent fractions, for example: 50%, 2%, 6%, etc.
  • d. Decimal fraction, for example: 0.50

DISCUSSION

3 5/6+(−1 1/6)

= 23/6 + (-7/6)

= 23/6 - 7/6

= 16/6

= 8/3

= 2 2/3

Conclusion:

So, The result of 3 5/6+(−1 1/6) is 2 2/3.

Learn more:

mampir ke indo :v

  1. Example of Fraction Problem: https://brainly.co.id/task/14280048
  2. Example of Fraction Subtraction Problem: https://brainly.co.id/task/23345402
  3. Material about fractional equations: https://brainly.co.id/task/3304077

______

Answer Details:

  • Grade: 4 Elementary School
  • Subject: Math
  • Material: Chapter 6 -Shards
  • Categorization Code: 4.2.6

Keywords: Subtract mixed fractions.

ACCESS MORE